Design issues in fuzzy case-based reasoning - Slonim, T.Y.; Schneider, M. (Fuzzy sets and systems, 2001)
This paper focuses on the aspect of case representation in case-based reasoning systems. We introduce an augmentation in which each case is weighted individually over an independent set of properties. In addition, we encourage the use of fuzzy-valued properties, and show their incorporation in this representation. Combining these two characteristics, we receive the framework for a versatile Fuzzy CBR system.